Trimaximal neutrino mixing from modular A4 invariance with residual symmetries - P.P. Novichkov; S.T. Petcov; M. Tanimoto (Physics Letters B, 2019)
We construct phenomenologically viable models of lepton masses and mixing based on modular A4 invariance broken to residual symmetries Z3T or Z3ST and Z2S respectively in the charged lepton and neutrino sectors. In these models the neutrino mixing matrix is of trimaximal mixing form. In addition to successfully describing the charged lepton masses, neutrino mass-squared differences and the atmospheric and reactor neutrino mixing angles θ23 and θ13, these models predict the values of the lightest neutrino mass (i.e., the absolute neutrino mass scale), of the Dirac and Majorana CP violation (CPV) phases, as well as the existence of specific correlations between i) the values of the solar neutrino mixing angle θ12 and the angle θ13 (which determines θ12), ii) the values of the Dirac CPV phase δ and of the angles θ23 and θ13, iii) the sum of the neutrino masses and θ23, iv) the neutrinoless double beta decay effective Majorana mass and θ23, and v) between the two Majorana phases.